Construction and characterization of a bovine BAC library with four genome-equivalent coverage - Eggen, André (BioMed Central, 2001)
A bovine artificial chromosome (BAC) library of 105 984 clones has been constructed in the vector pBeloBAC11 and organized in 3-dimension pools and high density membranes for screening by PCR and hybridization. The average insert size, determined after analysis of 388 clones, was estimated at 120 kb corresponding to a four genome coverage. Given the fact that a male was used to construct the library, the probability of finding any given autosomal and X or Y locus is respectively 0.98 and 0.86. The library was screened for 164 microsatellite markers and an average of 3.9 superpools was positive for each PCR system. None of the 50 or so BAC clones analysed by FISH was chimeric. This BAC library increases the international genome coverage for cattle to around 28 genome equivalents and extends the coverage of the ruminant genomes available at the Inra resource center to 15 genome equivalents.